ANALISIS PRIORITAS PEMELIHARAAN JALAN KOTA KOTAMOBAGU MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Mananoma, Tiny; Fithra Mokoagow, Abdul; Mokoginta, Gita Virginita; Damopolii, Virgina Dian Bayanasari (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
Roads infrastructure has a very important role in supporting economic, social and cultural activities of a region. Road maintenance is an activity related to road maintenance and repairs that are necessary and planned to maintain road conditions so it can be function optimally to serve traffic during the lifespan of the road. Kotamobagu Government has limitations in road maintenance, including the budget provided by the APBD is very limited, and policy makers in determining maintenance have not been based on objective assessments and the assessment of determining road maintenance priorities is still based on subjective assessments and have not based on accountable standards yet. Therefore, it is necessary to have a strategy for determining road priorities based on objective assessments and precise criteria. The research use Analytical Hierarchy Process (AHP) method as a determinant of the priority order for road maintenance in Kotamobagu. The criteria that being used are road conditions, annual average daily traffic (LHR) and handling costs. Collecting data was taken through direct submission to the Departmen of Public Works and Urban Planning, interviews and filling out questionnaires to relevant stakeholders.